2022
DOI: 10.1093/ofid/ofac154
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus 2 Infections by Race and Ethnicity in Arkansas

Abstract: Objective To estimate SARS-CoV-2 infection rates in Arkansas, a small rural state, using SARS-CoV-2 antibody prevalence as an indicator of infection. Study Design We collected residual serum samples from adult outpatients seen at hospitals or clinics in Arkansas for non-COVID-19-related reasons. A total of 5,804 samples were identified over three time periods: August 15-September 5 (time period 1), September 12-October 24 (ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These results may be related to the intensity of immune response between different races to produce antibodies against the SARS-CoV-2 infection ( 35 , 36 ). Previous study has shown that Hispanics and Blacks had higher rates of SARS-CoV-2 antibodies than Whites, indicating that SARS-CoV-2 spread disproportionately in racial and ethnic minorities during the COVID-19 pandemic ( 37 , 38 ). Future studies should further explore the possible molecular mechanisms ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 96%
“…These results may be related to the intensity of immune response between different races to produce antibodies against the SARS-CoV-2 infection ( 35 , 36 ). Previous study has shown that Hispanics and Blacks had higher rates of SARS-CoV-2 antibodies than Whites, indicating that SARS-CoV-2 spread disproportionately in racial and ethnic minorities during the COVID-19 pandemic ( 37 , 38 ). Future studies should further explore the possible molecular mechanisms ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 96%